Hormone Receptor Status May Impact the Survival Benefit Between Medullary Breast Carcinoma and Atypical Medullary Carcinoma of the Breast: A Population-Based Study - Qin, Wenxing; Qi, Feng; Guo, Mengzhou; Wang, Liangzhe; Zang, Yuan-Sheng (Frontiers in Oncology, 2021)
Background: A rare subtype of breast cancer, Atypical Medullary Carcinoma of the Breast (AMCB), showed a highly adverse prognosis as compared to Medullary Carcinoma of the Breast (MBC). The current study aimed to establish a correlated nomogram for the identification of the prognostic factors of AMCB and MBC. Methods: The Kaplan-Meier and Cox regression analysis were applied to the data acquired from the Surveillance, Epidemiology and End Results (SEER) database for 2004 to 2013 to analyze tumor characteristics and overall survival. Propensity-matching (PSM) analysis was performed to determine the overall survival (OS) among those with AMCB and MBC. A predictive nomogram was created and the concordance index (C-index) was used to predict accuracy and discriminative ability. Results: 2001 patients were diagnosed with MBC between 2004 to 2013 from the SEER database, including 147 patients diagnosed with AMCB. The number of diagnoses has gradually increased in both groups. Cox analysis of multivariate and Kaplan-Meier analysis showed that the older age (HR=3.005, 95% CI 1.906-4.739) and later stage were significantly associated with poor prognosis, while cancer directed surgery was an independent protective factor (HR=0.252, 95% CI 0.086-0.740). In the HR-negative stratification analysis, the older age (HR=2.476, 95% CI 1.398-4.385), later stage and histological type (HR=0.381, 95% CI 0.198-0.734) were found to be independent prognostic factors for low standard survival. The log-rank analysis demonstrated significantly worse prognostic factors for patients with AMCB than those with MBC (P=0.004). A nomogram (C-index for survival=0.75; 95% CI 0.69-0.81) was established from four independent prognostic factors after complete identification. Conclusions: MBC is rare, and cancer-directed surgery, older age, and later stage are independently linked with prognosis. In the HR negative population, AMCB patients earn a worse survival gain than those with MBC.